Multipurpose room interior noise control for owners and facility managers - Seip, Clare Elizabeth (Kansas State University, 2007)
Throughout recent years, to minimize the cost of construction, a large number of multipurpose spaces have been built using lightweight, less expensive materials without considering or designing for noise control to mitigate any sound that is loud, unpleasant, unexpected, or undesired yet after construction is completed, noise issues are often evident within the space and, if severe enough, may render the intended function of the structure useless. To address this problem, this report is intended to introduce Owners and Facility Managers to some of the common solutions to resolve noise issues in multipurpose rooms. The report focuses on solutions for existing projects primarily, but it is also sensitive to budget constraints and the impact of renovation. Typical multipurpose rooms researched have a volume of 50,000-150,000 cubic feet and are expected to be used for speech activities, small music functions, and some physical sports activities. Therefore, this report will introduce the fundamentals of sound and room acoustics including interior surface materials and construction. Also included are typical noise issues from interior sources, solutions that can be taken within the building to attenuate noise, and the trade-offs associated with each solution.
Keywords: Noise Control; Room Acoustics; Multipurpose Room; Architecture (0729); Engineering, General (0537); Physics, Acoustics (0986)